Counterstrike / 4 - Black, Peter Jay (Bloomsbury, London, 2016)
Deep beneath London, five extraordinary youths, orphans who bonded over their shared sense of justice, have formed the Urban Outlaws and dedicated themselves to outsmarting criminals and performing Random Acts of Kindness (R.A.K.s). The Urban Outlaws face their biggest challenge yet. They have to break into the Facility and find the ultimate weapon - Medusa - before Hector does. But there are five levels of security to crack and a mystery room that has Jack sweating whenever he thinks about it. But the clock is ticking. Hector is determined to have the weapon and release doomsday, and it is down to the Urban Outlaws to stop him. Can Jack come up with a plan in time?
Keywords: Fiction; JUVENILE FICTION; Science & Technology